Multifractal Characterization of Pore Size Distributions of Peat Soil - Joko Sampurno; Azrul Azwar; Fourier Dzar Eljabbar Latief; Wahyu Srigutomo (Journal of Mathematical and Fundamental Sciences, 2016)
This paper discusses a multifractal analysis of the microscopic structure of peat soil. The aim of this study was to apply the multifractal technique to analyze the properties of five slices of peat soil (L1-L5). Binary images (220 x 220 pixels, with a conversion value of 9.41 Î¼m/pixel) were made from the thin slices and then analyzed. This analysis was conducted to obtain the relationship between physical parameters and complexity parameters. The results showed that the spectrum of f(Î±) can describe well the pore size distribution and average size of pores correlated with the value of D(0). A high value of the average pore size is followed by a low D value and vice versa.